2001
DOI: 10.1002/1521-3846(200105)21:2<129::aid-abio129>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Dechlorination of TetrachloroetheneInfluence of Tetrachloroethene and Methane in Batch Cultivation under Methanotrophic Conditions in the Presence of Oxygen

Abstract: The feasibility of combining the reductive dechlorination and oxidative mineralization of tetrachloroethene (PCE) within one system was investigated in non-shaken methanotrophic batch cultivated cell suspensions. In the presence of up to 90% [v/v] methane and 10% [v/v] oxygen in the headspace, 200, 400 and 500 µmol/l PCE were completely dechlorinated over 100 days of incubation with 1% [v/v] activated sludge derived from a municipal wastewater treatment plant (equivalent to 6 mmol/l carbon). Meanwhile nearly 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
3
1

Year Published

2006
2006
2008
2008

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 25 publications
1
3
1
Order By: Relevance
“…When observed in a static position immediately after the addition of pure oxygen, the bottles contained two layers of biomass; one layer settled to the bottom of the bottles while the other layer was at the biomedium/headspace interface. Similar observations have been made by Klag et al 20 Based on this observation it was thought that the suspended biomass was aerobic bacteria utilising the oxygen added to the bottles, while the bottom layer consisted of anaerobic bacteria shielding from the oxygen. Addition of pure oxygen had a significant effect on PCE degradation (Fig.…”
Section: Resultssupporting
confidence: 80%
See 4 more Smart Citations
“…When observed in a static position immediately after the addition of pure oxygen, the bottles contained two layers of biomass; one layer settled to the bottom of the bottles while the other layer was at the biomedium/headspace interface. Similar observations have been made by Klag et al 20 Based on this observation it was thought that the suspended biomass was aerobic bacteria utilising the oxygen added to the bottles, while the bottom layer consisted of anaerobic bacteria shielding from the oxygen. Addition of pure oxygen had a significant effect on PCE degradation (Fig.…”
Section: Resultssupporting
confidence: 80%
“…Moreover, in this study oxygen was added intermittently to serum bottles. This was different from the constant 10% (v/v) oxygen concentration maintained in the study carried out by Klag et al 20. In this study, it is possible that the production of methane (results not shown) and ethylene detected in the serum bottles, combined with the addition of oxygen, may have either induced synthesis of methane or alkene monooxygenases, enzymes responsible for the aerobic co‐metabolic degradation of TCE, cis ‐DCE and VC, or promoted autotrophic growth on VC.…”
Section: Resultscontrasting
confidence: 68%
See 3 more Smart Citations